Accurate calculation of the eigenvalues of non-uniform strings and membranes - Amore, Paolo (2012)
We describe a pseudospectral approach which combines a mapping procedure with the principle of minimal sensitivity to obtain accurate estimates for the eigenvalues of non-uniform strings and both uniform and nonuniform membranes. We illustrate the method on specific examples, including the case of a cross shaped membrane, with arms of infinite length.